Platelet-Rich Plasma for the Aesthetic Surgeon - Sand, Jordan P.; Nabili, Vishad; Kochhar, Amit; Rawnsley, Jeffrey; Keller, Gregory (Facial Plastic Surgery, 2017)
Platelet-rich plasma (PRP) is an autogenously harvested blood plasma containing concentrated levels of platelets and growth factors. PRP has been identified as a promising treatment for enhancing wound healing and has been used for decades in multiple medical specialties including cardiac surgery, oral surgery, ophthalmology, and orthopedic surgery. Growing evidence for multiple aesthetic surgery applications has recently been developed, particularly for hair restoration and skin rejuvenation. The goal of this article is to review the current medical literature on PRP and identify promising applications that may be integrated into a modern aesthetic surgery practice. The evidence for the use of PRP technology is rapidly expanding as a powerful therapy for select cosmetic surgery patients.
Keywords: platelet-rich plasma; hair restoration; aesthetic surgery